Effect of different organics on growth and yield of Ashwagandha (Withania somnifera Dunal) - Ram, D.; Chandra, R.; Thenua, O.V.S. (Annals of Agricultural Research, 2016)
An experiment was conducted during 2007-08 at Main Experimental Station of the University, Faizabad, Uttar Pradesh to find out the appropriate source of organic matter for increasing the root yield of ashwagandha (Withania somnifera Dunal). The trial was laid out in Randomized Block Design with 11 treatments, replicated thrice. On the basis of observation recorded during experimentation and data analyzed, it was concluded that application of pressmud 10 t/ha was found superior to the other treatments, resulting in maximum plant height (39.40), root length (18.53 cm), fresh root yield (18.97 q/h) and dry root yield (6.63 q/h). This treatment also improved physico-chemical properties of soil.